Approaches to developing mechanisms for medical care centralization at the interterritorial level - D. V. Fedyaev; F. S. Nikitin; S. A. Kovaleva; V. V. Omelyanovskiy (Фармакоэкономика, 2024)
Background. As new high-tech methods of treatment and diagnostics are introduced into the basic compulsory health insurance program, the focus on creating separate regional healthcare systems is becoming less effective. The creation of the necessary infrastructure requires disproportionately large investments, while the needs of the population in most regions do not provide adequate loading of newly created facilities. A promising solution to these problems is the centralization of delivering certain types of medical care (MC) on the basis of interregional medical centers.Objective: development of approaches to identifying medical interventions that are appropriate to provide in specialized interregional centers.Material and methods. The criteria for selection of medical interventions including MC profiles and diagnosis-related groups (DRGs) of diseases, which potentially require centralization were developed. On the basis of statistical analysis, data on specialized MC provided in inpatient settings by “Pediatric surgery” and “Traumatology and orthopedics” profiles were analyzed to identify regions with low and high levels of hospitalizations in order to determine the need for centralization or the creation of interregional centers.Results. The analysis enabled to identify the territorial subjects of the Russian Federation (RF) where the issue of MC centralization would be relevant to increase its availability to the insured population in the territory of certain subject. Besides, the study identified regions, in which the number of hospitalizations significantly exceeded the average indicators in the RF. It is advisable to create interregional MC centers on the basis of such subjects.Conclusion. The presented analysis of individual profiles and DRGs across the territorial subjects of the RF showed the objective differences in the extent of provided MC. The proposed methodology for determining DRGs and identifying subjects of the RF that have a surplus or deficit in the provision of MC can form the basis for approaches to identifying “MC centralization points”.